A Longitudinal Study of the Relationship Between Children's Lexical Acquisition, Socioeconomic Status and Classroom Environment. - Foster, Brandon. (2017)
Abstract: This thesis utilizes multilevel growth curve modeling to examine the impact of socioeconomic status (SES) and classroom environments on children's lexical development from the fall of preschool to the spring of kindergarten. Fitting with prior research finding that macro measures of SES (i.e., mother's highest level of education and family income) is predictive of children's lexical abilities, this study found that both mother's highest level of education and family income were predictive of children's initial level of lexical ability, but not changes in their abilities. This study also found that measures of classroom environment, specifically the Concept Development and Quality of Feedback subscales of the Classroom Assessment Scoring System (CLASS) predicted children's initial level of lexical abilities, but not changes in in lexical development across time. Findings and limitations are explored.; Thesis (M.A.)--Tufts University, 2013.; Submitted to the Dept. of Child Development.; Advisor: Calvin Gidney.; Committee: Christine McWayne, and Bruce Thompson.; Keywords: Developmental psychology, and Educational psychology.